Environmental Impact of Energy Diversification Using Refuse-Derived Fuel in Cement Industry - Firdausi, Eyda; Abdul Matin, Hashfi Hawali; Rachmawati, Siti; Wahyono, Yoyon; Purwono, Purwono; Budiyono, Budiyono; Kencanawardhani, Larasati Gumilang (Universitas Diponegoro, 2026)
Processing municipal solid waste into refuse-derived fuel (RDF) is an alternative solution to the waste problem. This study determined the potential environmental impact of Sleman RDF as an energy diversification agent in the cement industry using life cycle assessment (LCA). The boundary system of this study is gate-to-grave, with a functional unit of co-firing energy requirements for the production of 1 metric ton of clinker. Two clinker co-firing scenarios were developed, involving a combination of coal and alternative fuels. The results showed that the production of 1 metric ton of clinker requires a large amount of resources and contributes significantly to climate change, ecosystem toxicity, and human toxicity. Co-firing clinker in the alternative scenario successfully reduced the potential environmental impact by 14% with a thermal substitution rate of 20%. The findings of this study indicate that RDF is effective in reducing dependence on fossil fuels and lowering emissions and the potential environmental impact.